Problem Solving Therapy Improves Effortful Cognition in Major Depression - Jiang, Chenguang; Zhou, Hongliang; Chen, Limin; Zhou, Zhenhe (Frontiers in Psychiatry, 2021)
Background: Effortful cognition processing is an intentionally initiated sequence of cognitive activities, which may supply top-down and goal oriented reassessment of specific stimuli to regulate specific state-driven responses contextually, whereas automatic cognitive processing is a sequence of cognitive activities that is automatically initiated in response to an input configuration. The effortful-automatic perspective has implications for understanding the nature of the clinical features of major depressions. The aim of this study was to investigate the influence of the Problem solving therapy (PST) on effortful cognition in major depression (MD). Methods: Participants included antidepressant treatment (AT) group (n = 31) or the combined antidepressant treatment and PST (CATP) group (n = 32) and healthy controls (HCs) (n = 30). Hamilton Depression Rating Scale (HAMD, 17-item version) and the Face-vignette task (FVT) were measured for AT group and CATP group, at baseline (before the first intervention) and after 12 week interventions. The HC group was assessed with the FVT only once. At baseline, both patients and HCs were required to complete the Basic facial emotion identification test (BFEIT). Results: The emotion identification accuracy of HC group was higher than that of patient group when performed BFEIT; patients with MD present poor FVT performances; compared to antidepressant treatment, PST plus antidepressant treatment decreased HAMD scores and improved the FVT performances in patients with MD. Conclusions: Patients with MD present effortful cognition dysfunction, and PST can improve effortful cognitive dysfunction. These findings suggest that the measurement of effortful cognition might be one of indexes for therapeutic effect of PST in MD.